GOVERNMENT EFFORTS IN INCREASING BUSINESS COMPETITIVENESS AND MARKETING MSME PRODUCTS CASE STUDY IN KUNCIRAN INDAH VILLAGE PINANG DISTRICT, TANGERANG CITY - Dwi Meitari Hapsari; Bambang Kurniawan; Asep Sugara (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
This research aims to identify and explain the development of MSMEs, marketing strategies, and efforts to increase the competitiveness of MSME businesses in Kunciran Indah Village, Pinang District, Tangerang City. The research method uses a qualitative approach and key informants who come from sub-district officials and MSME business actors in Kunciran Indah Sub-district. The results of the research explain that the development of MSMEs in Kunciran Indah Village, Pinang District, Tangerang City is increasing from year to year, especially with the impact of the Covid-19 outbreak, where many people have been laid off or opened up new opportunities for business and developing MSMEs as an alternative livelihood . To increase business competitiveness, in addition to providing coaching and assistance by sub-districts and the Department of Industry, Trade, Industry and Cooperatives, there is also involvement of professional business actors and campuses. Apart from that, a UMKM outlet in Kunciran Indah Village was established with the name Pinang Beres which is integrated within the UMKM of Pinang District. The research suggestion is that the efforts of the Kunciran Indah Subdistrict Government in collaboration with the Pinang District and the Tangerang City Industry and Trade Service, regarding administrative guidance and assistance, capital and marketing, do not just stop following the cessation of the Covid 19 outbreak, because not all MSMEs have received the same opportunities, as well as MSMEs that Having received the opportunity, there are still many who need a continuous business assistance process.